Estimating Uncertainty of Economically Optimum N Fertilizer Rates - Martin Bachmaier; Markus Gandorfer (International Journal of Agronomy)
Nitrogen rate trials are often performed to determine the economically optimum N application rate. For this purpose, the yield is modeled as a function of the N application. The regression analysis is commonly used to estimate the modeled functions and the economic optimum rate, 𝑁opt. However, computer programs do not calculate confidence intervals for 𝑁opt derived from quadratic yield response model or other commonly used models. The objective was to develop a method for computing and interpreting confidence intervals for 𝑁opt. These confidence intervals can be estimated using an online program VINO.EXE. For the N rate trials on the experimental field Sieblerfeld (Bavaria), confidence intervals were computed for a range of wheat and N fertilizer prices and for selected N rates for quadratic and linear plateau models. The latter concerns the comparison with confidence intervals based upon the linear-plus-plateau yield regression model. All intervals were found to be unexpectedly wide and their ranges were affected by N rates used in the calculations and by the choice of yield response model.